Morphometric characterization of Long-Legged Buzzard (Buteo rufinus) of Pontastacus leptodactylusTongue and Heart Caracterización - Baygeldi, Saime Betuel; Kanmaz, Yesim Aslan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Morphometric and scanning electron microscopic evaluations reveal limitations in long-legged buzzards (Buteo rufinus), are particularly limited when it comes to the detailed morphological characteristics of the tongue and heart. The aim ABSTRACTof our study is to present these data in detail and to contribute to the anatomical formation of wildanimals,which are m tho te (DMT) p st cide is ne of th chemic ls use to particularly difficult to study. Four Long-Legged Buzzard (Buteo otect some agricul ural areas from ha mful organisms DMT rufinus) belonging to the Accipitridae family were used in this study. The tongues and hearts of the animals were dissected sidues released directly or i direc ly to th environment andmacro and micrometric analyses were performed. The use serious problems in natu e DMT residue mixed with the quaticenvronment adversly affecaquatic organismsand tongue of the Long-Legged Buzzard was distinctly elongated, terminating inan oval-shapedapex.Thetongue widths were is effect s car ied to humans hrough the food chain. In th s udy, oxidative stessresponses ducedbyDMTpesticiden 3.83 +/- 0.03mmat the apex lingua, 7.64 +/- 0.07mm at thecorpus were nvestigatedForths pu pose lingua and 9.09 +/- 0.04mm at the papillary apex. The total length xidativ stress and antioxdan p rameters Thiobarbituric acid of the tongue from the radix to the apex was 29.30 +/- 050 mm and the greatest thickness of the corpus was 2.89 +/- 16mm. The active substances (TBARS) Glutathione (GSH) Superox de length of the Long-Legged Buzzard heart from the apex to the base was 30.05 +/- 0.05mm, the thickness of thebase cordis smutase (SOD), catalase (CAT) and glutathione peroxidase was25.03 +/- 0.16 mmandthe thickness ofthe apex cordis was PX) caused by dimethoate (DMT) pesticide in10.95 +/- 0.09mm. 17 5, 35, and
Morfométrica de la lengua y el corazón del buitre pata larga (Buteo rufinus)
Keywords: Heart; Long-Legged Buzzard; morphometric; SEM; tongue